Nocturnal sleep duration and cognitive impairment in a population-based study of older adults - Loerbroks, Adrian; Amelang, Manfred; Stürmer, Til (International journal of geriatric psychiatry, 2010)
Objective: We aimed to investigate the association between nocturnal sleep duration, changes in nocturnal sleep duration and cognitive impairment in older adults. Methods: 4010 participants of a population-based cohort study provided information on nocturnal sleep duration at baseline (1991-1995) and at follow-up (2002/2003). 792 follow-up participants aged 70+ by 2006 participated in telephone-based cognitive assessments. Several cognitive tests were used including the telephone interview for cognitive status (TICS). Cognitive impairment was defined as <31 points on the TICS (13.0%) and as below this percentile on the other tests. Based on individual tests, a verbal memory score and a total score were constructed. Multivariable prevalence ratios (PRs) of cognitive impairment and 95% confidence intervals (95%CIs) were computed using Poisson regression. Analyses were restricted to those free of depression in 2002/2003 (n = 695). Results: Sleeping ≤6 or 8 h per night (versus 7 h) were unrelated to cognitive impairment. Sleeping ≥9 h was positively, although imprecisely, associated with impairment of verbal memory (PR = 1.7, 95%CI = 1.0, 3.0), and less pronounced with the other cognitive measures. An increase in sleep duration from 7-8 h in 1992-1995 to ≥9 h 8.5 years later (versus sleeping 7-8 h at both time points) was associated with an increased prevalence of cognitive impairment according to the TICS (PR = 2.1, 95% = 1.0, 4.5) and the verbal memory score (PR = 2.0, 95%CI = 1.0, 3.8). Conclusions: Increases in sleep duration are associated with cognitive impairment. A biological explanation for this association is currently lacking. Increases in sleep duration could be a marker of cognitive deficits. Copyright © 2009 John Wiley & Sons, Ltd.